STRATEGI KOMUNIKASI ALIH KODE DALAM INTERAKSI KARAKTER DRAMA TV: KASUS KHUSUS GOJI KARA KUJI MADE KARYA MIKI AIHARA - Rahman W.P, Abdul; Rahman, Fathu; Iswary, Ery (JURNAL ILMU BUDAYA, 2023)
This research discusses the English code-switching that occurs in the drama Goji Kara Kuji Made, which is the source of the research data. This research aims to: 1) explain the code-switching that occurs in the television drama Goji Kara Kuji Made, and 2) describe the factors that cause code-switching and the function of code-switching that appears in the television drama Goji Kara Kuji Made. This study used the descriptive-qualitative method. The theoretical framework referred to is based on the theory developed by Holmes (2008). Based on the results of the analysis, it is known that the factors causing code-switching are background, topic, the purpose of the interaction, and lexical borrowing. Meanwhile, the functions found in this research are solidarity, group membership, creating distance, quotation marks, emphasizing certain messages, affective functions, and filling lexical needs.